2014
DOI: 10.1108/jhom-04-2014-0064
|View full text |Cite
|
Sign up to set email alerts
|

Lean in healthcare – history and recent developments

Abstract: Abstract:The performance gap between hospital spending and outcomes is indicative of inefficient care delivery. Operational failures-breakdowns in internal supply chains that prevent work from being completed-contribute to inefficiency by consuming 10% of nurses' time (Hendrich et al. 2008, Tucker 2004. This paper seeks to identify organizational factors associated with operational failures, with a goal of providing insight into effective strategies for removal. We observed nurses on medical/ surgical units at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…Lean management is considered a management system aims to organize the operation design which reduced waste and time-consuming, improved safety and quality, and decreased the costs in health industries by using several tools such as Fishbone, flow chart in addition to redesign the operational work (Costaet al, 2017;D'Andreamatteo et al, 2015). Many health organizations such as National Health Service (NHS) and Institute for Healthcare Improvement (IHI) have recommended utilizing the lean concepts in health setting to enhance work efficiency (Costa et al, 2017;D'Andreamatteo et al, 2015;Machado et al, 2013;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lean management is considered a management system aims to organize the operation design which reduced waste and time-consuming, improved safety and quality, and decreased the costs in health industries by using several tools such as Fishbone, flow chart in addition to redesign the operational work (Costaet al, 2017;D'Andreamatteo et al, 2015). Many health organizations such as National Health Service (NHS) and Institute for Healthcare Improvement (IHI) have recommended utilizing the lean concepts in health setting to enhance work efficiency (Costa et al, 2017;D'Andreamatteo et al, 2015;Machado et al, 2013;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The literature showed that lean healthcare has been growing into a significant strand of research and quality projects in the early 2,000s.it is considered a most common tool used to ensure cost effectiveness and removal of wastes, and to enhance patient and employee satisfaction. (Costa et al, 2017;D'Andreamatteo et al, 2015;Lawal et al, 2014;Sloan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Supply chain integration and tenets of lean philosophy have increased quality and productivity in many service industries. Lean philosophy has already been applied to healthcare conceptual articles (Peters, 2014;Sloan et al, 2014), and in empirical studies (Toussaint and Berry, 2013;Ulhassan et al, 2014), but it has been done in a piecemeal manner focusing on a few aspects of the hospital ecosystem. Lean implementation in hospitals still has challenges (Kaplan et al, 2014;Lawal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The author believes that hospitals can be significantly improved by implementing LSs, as shown in the reviewed literature (Al-Balushi et al, 2014). Indeed, according to recent studies, LSs can help healthcare providers to cut waste and improve services, leading to a better patient experience and lower resource usage (Sloan et al, 2014). However, in order to introduce LSs to ED staff, who might not have heard of LSs before, it would be wise to obtain an understanding of the current quality practices within their EDs.…”
mentioning
confidence: 99%